Territorial Innovation in Less Developed Regions Governance, Technologies, and Sustainability - Teles, Filipe; Rodrigues, Carlos; Ramos, Fernando; Botelho, Anabela (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book examines the roles of communities in the general framework of territorial innovation, particularly in the context of less developed regions. With a specific focus on Portugal, it offers conceptual improvements that will be of use to other European regions. The book will appeal to scholars and students of regional governance and politics, from public administration to economics, sociology, geography and political science, as well as to practitioners. Filipe Teles is Pro-Rector for Regional Development and Urban Policies at the University of Aveiro. Fernando Ramos is Professor of Communication Sciences and Technologies at the University of Aveiro. Carlos Rodrigues is Associate Professor and Head of the Department of Social, Political and Territorial Sciences at the University of Aveiro. Anabela Botelho is Professor of Economics at the University of Aveiro. .
1. Community-led innovation: facts, rhetoric, and policy challenges -- Part 1: Models -- 2. New Models of Innovation in Old Industrial Regions -- 3. On the Performance of Regional Innovation Systems -- 4. Social Tipping Dynamics for disruptive innovation policies towards a stable climate scenario -- 5. Digital technologies and mediation in the context of territorial innovation -- 6. Towards an integrated conceptual framework of Territorial Innovation in Less Developed Regions: the Sustainable Regions' approach -- Part 2: Tools -- 7. Digitalisation in a multilevel governance context: the case of Cohesion Policy -- 8. Prototyping a digital platform to promote mediation practices in the territory -- 9. The role of strategic environmental assessment for sustainability in urban systems transformation -- Part 3: Policy and actors -- 10. The role of state and non-state actors in ensuring the effectiveness of innovation policy -- 11. European Urban Agenda: The Predicaments of Decentralised Coordinative Action -- 12. Local Development through entrepreneurship and innovation ecosystems -- 13. Tourism and development in lagging regions -- 14. Territorial Cohesion and Innovation: a needed dialogue.
Keywords: Political planning; Political science; Sustainability; Public Policy; Governance and Government; Sustainability